Single nucleotide polymorphism (SNP) in genes of lupus: A Philippine study (SIGLA‐PH). Issue 1 (19th January 2022) - Tee, Michael L.; Tee, Cherica A.; Nevado, Jose B.; Santiago, Angeline Therese; Abrilla, Aedrian A.; Lapid, Carlo M.; Tablizo, Francis A.; Dizon, Joshua A.; Morado, El K. B.; Cutiongco‐Dela Paz, Eva Maria
Abstract: Background: Systemic lupus erythematosus (SLE) is a complex prototypic autoimmune disease, with a prevalence of 20–150 per 100, 000, most commonly affecting women at child‐bearing age. Genome‐wide association studies and fine mapping of candidate regions have paved the way for greater understanding of SLE as a disease of genetic–environmental susceptibility and the functions of the genes involved. Method: This study was conducted to determine the association of selected single nucleotide polymorphisms (SNPs) from established genomic databases based on theoretical risk and protective odds ratios > 2.5 or <0.40) to susceptibility of developing SLE among Filipinos. Results: We analyzed data from 310 SLE patients and 318 controls. We identified eight significant SNPs namely rs9271100, rs9271366, rs9272105, rs9275328, rs2647087, rs12734338, rs17885098, and rs3883013 to be associated with an increased risk of developing SLE among Filipinos. Conclusion: Eight SNPs were found to be associated with the development of SLE among Filipinos. Similar to previous genetic studies in lupus patients, majority of the SNPs were found in the major histocompatibilty complex genes in the HLA region. Our study identified two unique SNPs that will be validated as potential diagnostic markers for SLE. The findings of this study may contribute to the development of a polygenic risk score in determining susceptibility to SLE among Filipinos. Abstract : Supported by a research grant from the Department of Science and Technology Philippine Council for Health Research and Development Key points: Eight SNPs, namely rs9271100, rs9271366, rs9272105, rs9275328, rs2647087, rs12734338, rs17885098, and rs3883013, were found to be associated with an increased risk of developing SLE among Filipinos.